MAPPING ICD-11 (THE 11TH INTERNATIONAL CLASSIFICATION OF DISEASE) TO ICD-10-KM-7TH (THE KOREAN MODIFICATION 7TH OF THE ICD-10) FOR FLEXIBLE TRANSITION TO ICD-11. - Lee Hyunkyung (Perspectives in Health Information Management)
In the World Health Congress in May 2019, ICD-11 was approved, This study aims to analyze the classification system of the 11th revision of the International Classification of Disease mapping with the ICD-10-KM-7th (ICD-10 Korean Modification 7th) to identify the characteristics of ICD-11 so that it can be flexibly linked to KCD-7 when introduced in Korea. The mapping was conducted based on the ICD-11 frozen version (April 2019). Most of the ICD-11 codes were mapped to a single ICD-10 or KCD-7 code. However, for the diabetes code, more than 80 percent of KCD-7 codes needed to be mapped to one or two post-coordination codes, along with one stem code in ICD-11. ICD-11 is a great classification that has an excellent taxonomy system to express detailed information. For the codes that have been changed or removed, a proper guideline might also be useful for users to understand the changes made in KCD-7 or ICD-10 code.